Adolescentes na contemporaneidade : desamparo e laços fragilizados em meio aos "ideais" da sociedade de consumo - Gomes, Vinicius Romagnolli Rodrigues (2014)
The proposal of this dissertation is to understand the adolescence at contemporaneity by a psychoanalytic approach articulated to social perspective, which comprises the adolescence as a specific configuration of the historic structure, i.e, a subject who builds on / by the relationship with the other, through social and cultural via, as well by identificatory processes. From Sigmund Freud's work (1856-1939) and other contemporary psychoanalysts and sociologists, our purpose is to understand the contemporary social background, whose ideals have been forged by consumer society, which its own mouthpiece is indeed the cultural industry, producing subjective impacts on adolescents. The concept of ideal by psychoanalytic perspective is a "border-concept" that highlights the psychic subject's social dimension, i.e, the ideals point to the place where the other occupies for subject's constitution, and they shall be the culture's guiding elements, also providing references about what has to be pursued. However, our hypothesis is that contemporaneity's ideals have not fulfilled either their function for protection and for promoting social bonds like it was proposed by Freud (1930/2010). Instead, they have intensified adolescents' sense of helplessness, making the social ties' building more difficult, and throwing them to seek for shelter through consumerism and virtuality. They also seek for emotional links through ephemeral group arrangements or social networks on the internet (among those social network, the emphasis is placed on Facebook). Investing in commodities and images from the internet or Facebook or being part of fads, or group formation, which presents a massive and standardized manners and behaving, teenagers (adolescents) do not invest in the human / real "other" and it presents consequences: atrophy of symbolization ability, disability of contacting with reality and the objectal divestment. All these considerations have drawn to the negative narcissism concept by A. Green (1988) which represents an (inefficient) defense condition against the traumatic contemporary scenario, which is also a psychic expression of contemporary ill-feeling. This analysis presents a social and clinical relevance, since it shall contribute to enhance the comprehension either by the society, about contemporary adolescents, or by psychologists whose everyday clinics receive this kind of audience.